Activation of SK3 channel plays a pivotal role in modulation of trigeminal neuralgia. (2nd December 2021) - Zhao, Jiaomei; Zhang, Yue; Liu, Xiangbo; Rao, Yong; Fu, Jia; Hua, Lu; Ou, Cehua
ABSTRACT: Objective: To investigate whether small conductance Ca 2+ activated K+ channels; Trigeminal ganglion; Trigeminal neuralgia. (SK3) exists in normal rats' trigeminal ganglions (TG) and its effect on their pain thresholds. Methods: In total, 110 healthy adult male Sprague–Dawley (SD) rats were involved in this study. Ten rats were dissected to collect their liver tissues, TG and DRG. The rest of the rats were randomly assigned to either the experimental group or the control group. The animal model of trigeminal neuralgia (TN) was established by infraorbital nerve ligation. The expression of SK3 channels in their livers, TG and dorsal root ganglions (DRG) were detected. And different doses of SK3 channel activator and inhibitor were administered to the rats in both groups 15 days after the operation; meanwhile, their pain thresholds were also measured. Results: The expression of SK3 channel was found in TG. In the experimental group, the pain threshold was significantly decreased and there was a decreased level of SK3 than that in the control group at 15 days after operation. The administration of SK3 channel agonist (CyPPA) could significantly improve the pain threshold, while, the pain threshold decreased after administration of SK3 channel antagonist (Apamin). Conclusion: The SK3 channel may play a pivotal role in the pathogenesis of trigeminal neuralgia, and it may be one of the potential targets for the treatment of trigeminal neuralgia.